Early ontogeny of humeral trabecular bone in Neandertals and recent modern humans. Issue 154 (May 2021) - Chevalier, Tony; Colard, Thomas; Colombo, Antony; Golovanova, Liubov; Doronichev, Vladimir; Hublin, Jean-Jacques
Abstract: Trabecular bone ontogeny is well known in modern humans and unknown in Neandertals. Yet the bone developmental pattern is useful for interpreting fossils from evolutionary and functional perspectives. Interestingly, microstructure in early ontogeny is supposedly not influenced by high and specific mechanical loading related to the lifestyle of a human group and consequently does not directly depend on the activities of hunter-gatherers. Here, we specifically explored the early growth trajectories of the trabecular bone structure of the humerus and emphasized in particular how bone fraction (bone volume/total volume [BV/TV]) was built up in Neandertals, given the specific modern human bone loss after birth and the use of BV/TV in functional studies. Six Neandertals and 26 recent modern humans ranging from perinates to adolescents were included in this study. Six trabecular parameters were measured within a cubic region of interest extracted from the proximal metaphysis of the humerus. We found that the microstructural changes in Neandertals during early ontogeny (<1 year) fit with modern human growth trajectories for each parameter. The specific bone loss occurring immediately after birth in modern humans also occurred in Neandertals (but not in chimpanzees). However, the early childhood fossil Ferrassie 6 presented unexpectedly high BV/TV, whereas the high BV/TV in the Crouzade I adolescent was predictable. These results suggest that Neandertals and modern humans shared predetermined early growth trajectories and developmental mechanisms. We assume that the close relationship between skeletal characteristics in early ontogeny and adults in modern humans also existed in Neandertals. However, it was difficult to ensure that the high BV/TV in Neandertal early childhood, represented by only one individual, was at the origin of the high BV/TV observed in adults. Consequently, our study does not challenge the mechanical hypothesis that explains the trabecular gracilization of the humerus during the Holocene.